Analisis Faktor-Faktor Yang Mempengaruhi Keberhasilan Wirausaha Di Sektor Pertanian - Sutrisno Sutrisno; Asruni Azis; Dasmaniar Dasmaniar; Sangkala Irwan (JIMAD : Jurnal Ilmiah Multidisiplin, 2026)
ABSTRACT This study aims to analyze the factors influencing entrepreneurial success in the agricultural sector. The agricultural sector plays a vital role in the community's economy, but the success of agricultural businesses is influenced by various internal and external factors. This study used a quantitative approach with a descriptive-analytical design. Data were collected through questionnaires distributed to agricultural business owners and analyzed using descriptive statistics and simple linear regression. The results indicate that business capital, education level, business experience, innovation, access to technology, and government support significantly influence entrepreneurial success in the agricultural sector. Innovation and business management skills are the dominant factors determining business development. Furthermore, motivation and the ability to adapt to market changes also influence the sustainability of agricultural businesses. This study concludes that entrepreneurial success in the agricultural sector is not solely determined by economic factors but also by skills, creativity, and a supportive business environment. Therefore, entrepreneurship training, access to capital, and government policy support are needed to increase the success of agricultural entrepreneurs. Keywords: Entrepreneurship, Agriculture, Business Success, Innovation, Agricultural Entrepreneurship